The adventures of Beekle : The Unimaginary Friend (Hachette Audio, Little, Brown and Company, 2015)
An imaginary friend waits a long time to be imagined by a child and given a special name, and finally does the unimaginable--he sets out on a quest to find his perfect match in the real world.

Crenshaw (Feiwel and Friends, Listening Library, Penguin Random House, Feiwel & Friends, Books on Tape, Thorndike Press Large Print, 2018)
Jackson and his family have fallen on hard times. There's no more money for rent. And not much for food, either. His parents, his little sister, and their dog may have to live in their minivan. Again. Crenshaw is a cat. He's large, he's outspoken, and he's imaginary. He has come back into Jackson's life to help him. But is an imaginary friend enough to save this family from losing everything?

Sunday's at Tiffany's (Hachette Audio, Little, Brown and Company, Little, Brown, Grand Central Pub, Books on Tape, Grand Central Publishing, 2009)
Years after spending a lonely childhood at the side of a make-believe best friend named Michael, theater maven's daughter Jane encounters a loving flesh-and-blood Michael who is exactly like the figure of her childhood imagination.

The horse in Harry's room (An Early I can read book, ,, 1970)
Although no one else could see it, Harry was very pleased to have a horse in his room.

We Forgot Brock! (Simon & Schuster Books for Young Readers, 2017)
Phillip and Brock are best friends, although everyone else thinks Brock is imaginary, so when Phillip gets tired out at the Big Fair while Brock is still having fun, they are separated and it will take a very special twosome to bring them back together again.

Jessica (Picture puffins, ,, 1990)
Ruthie does everything with her imaginary friend Jessica; then, on her first day at kindergarten, she meets a real new friend with the same name.
CD: track 1: narration with page turn signals , track 2: narration with no page turn signals.

Dory Fantasmagory: Dory Dory black sheep Vol 3 (Dory Fantasmagory, 3, 1, 2016)
Ever since Dory met Rosabelle, a real true friend whose imagination and high spirits match her own, school has been pretty good. But now the class is learning to read, and it's proving to be a challenge for Dory. While Rosabelle can read chapter books in her head, Dory is stuck with baby books about a happy little farm. Dory wishes for a potion to turn her into a reader but things don't go as planned. Suddenly, a naughty little girl who looks an awful lot like Dory's imaginary nemesis, Mrs. Gobble Gracker, shows up. And a black sheep leaves the pages of the farm book to follow Dory to school. It really needs her help--this seems like a job for a superhero! And it would help if she knew how to read.

Dory Fantasmagory Vol 1 (Dory Fantasmagory, 1, 1, 2014)
Dory, the youngest in her family, is a girl with a very active imagination, and she spends the summer playing with her imaginary friend, pretending to be a dog, battling monsters, and generally driving her family nuts.

When a dragon moves in (When a Dragon Moves In, ,, 2015)
A young boy builds a sand castle on the beach and a dragon moves in. The boy and the dragon spend the day at the shore flying a kite, braving the waves, defying bullies, and roasting marshmallows, while the boy's parents remain occupied nearby with their own pastimes. When no one believes the boy's story about the dragon, the creature launches into a mischievous mode and wreaks havoc on everything in its path-- or is it all in the boy's imagination?

Brightwood (Recorded Books, Inc., Workman Publishing Company, Algonquin Young Readers, 2016)
When her mother disappears and a menacing stranger tries to claim her home, Brightwood Hall, for himself, Daisy must use her wits, courage, and help from her imaginary friends to survive.

A wee boo (Orca Book Publishers, 2022)
"A humorous picture book about a ghost who is too cute to be scary and who realizes that she might have a more important future as an imaginary friend" --

Skeleton tree (Skeleton Tree, ,, 2019)
"Twelve-year-old Stanly knows the bone growing in his yard is a little weird, but that's okay, because he'll have the perfect photo to submit to the Young Discoverer's Competition. With such a unique find, he's sure to win the grand prize. But, oddly, the bone doesn't appear in any photos. Even stranger, it seems to be growing into a ful skeleton...one that only children can see. There's just one person who doesn't find any of this weird--Stanly's little sister. Mischievous Miren adopts the skeleton as a friend, and soon the two become inseparable playmates. When Miren starts to grow sick, Stanly suspects that the skelton is responsible and does everything in his power to drive the creature away. However, Miren is desperate not to lose her friend, forcing Stanly to question everything he's ever believed about life, love, and the mysterious forces that connect us."--Back cover.

Imaginary (Recorded Books, Inc., Abrams, Amulet Books, 2021)
Eleven-year-old Zach knows he is too old to have an imaginary playmate, but between grieving for the loss of his father and coping with bullying at school the only place he seems to find joy is in his fantasy world with his best friend Shovel.

Inkling (Alfred A. Knopf, Random House/Listening Library, Findaway World, LLC, 2018)
The Rylance family is stuck. Dad's got writer's block. Ethan promised to illustrate a group project at school--even though he can't draw. Sarah's still pining for a puppy. And they all miss Mom. So much more than they can say. Enter Inkling. Inkling begins life in Mr. Rylance's sketchbook. But one night the ink of his drawings runs together--and then leaps off the page! This small burst of creativity is about to change everything. Ethan finds him first. Inkling has absorbed a couple chapters of his math book--not good--and the story he's supposed to be illustrating for school--also not good. But Inkling's also started drawing the pictures to go with the story--which is amazing! It's just the help Ethan was looking for! Inkling helps the rest of the family too--for Sarah he's a puppy. And for Dad he's a spark of ideas for a new graphic novel. It's exactly what they all want. It's not until Inkling goes missing that this family has to face the larger questions of what they--and Inkling--truly need.

Dory Fantasmagory: and the real true friend Vol 2 (Dory Fantasmagory, 2, 1, 2015)
Dory, a highly imaginative youngest child, makes a new friend at school but her brother and sister are sure Rosabelle is imaginary, just like all of Dory's other friends.

The Snurtch (Atheneum Books for Young Readers, 2016)
"Ruthie has a problem at school. It is the Snurtch. The Snurtch is a scribbly, grabby, rude monster who follows Ruthie around and gets her into all sorts of trouble. It seems Ruthie will never be rid of the Snurtch. But eventually, she realizes she's not the only one... George has one too"--

Dotty (Abrams, Abrams Books for Young Readers, 2016)
Ida's imaginary friend, Dotty, is tied to her with a blue string and when Ida's classmates tease her about Dotty, Ida is surprised to discover that her teacher carries a red string with her wherever she goes.

A cool moonlight (Dial Books, 2003)
Eight-year-old Lila, born with xeroderma pigmentosum, a skin disease that makes her sensitive to sunlight, makes secret plans to feel the sun's rays on her ninth birthday.

Yukon ho!: a Calvin and Hobbes collection (Andrews and McMeel, 1989)
Calvin--a six-year-old boy with a boundless imagination and a zest for misadventure--confounds his parents, his teacher and his classmates with the help of his lovable stuffed tiger Hobbes

Trigwater Did It (Morrow Junior Books, 1989)
Arnie's invisible friend Trigwater gets him into all sorts of trouble until Arnie decides to make him behave.